1821 Ga. Laws 599 - (:unkn) unknown (My University, 1816)
Div. 10, § 19: Prohibited the carrying of any pistol, hanger, cutlass, bludgeon, or other offensive weapon with the intent to assault a person. Punishable by imprisonment with hard labor for a period of time to be determined by a jury.
Keywords: CARRY - INTENT TO COMMIT CRIME